Novel Industry 4.0 Technologies and Applications - Papakostas, Nikolaos; Constantinescu, Carmen; Mourtzis, Dimitris (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The Industry 4.0 paradigm has led to the creation of new opportunities for taking advantage of a set of diverse technologies in the manufacturing domain. This book touches on a series of advanced technologies and research fields, including Internet of Things, Augmented and Virtual Reality, Machine Learning, Advanced Robotics, Additive Manufacturing, System and Process Simulation, Computer-Aided Design/Engineering/Manufacturing/Process Planning Systems as well as Product Lifecycle Management Platforms. The topics covered span a series of diverse areas related to a) product design and development, b) manufacturing systems and operations, c) process engineering, and d) Industry 4.0 technologies review and realization.